1991
DOI: 10.1063/1.349184
|View full text |Cite
|
Sign up to set email alerts
|

Electroreflectance study of a symmetrically coupled GaAs/Ga0.77Al0.23As double quantum well system

Abstract: Electroreflectance spectroscopy has been used to study a GaAs/Ga0.77Al0.23As symmetrically coupled double quantum well system as a function of externally applied electric field. Both intra- and inter-well exciton transitions were detected. The energy shifts of the coupled quantum confined levels are in good agreement with a theoretical calculation. Details of the lineshape fit yield important information about the modulation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Upon further increase of the reverse bias voltage, the ER exhibits a change of phase between -4 and -5 V. This phase change can be understood as follows. It has been shown that for an excitonic transition from a QW, the ER signal is related to the first derivatives of the transition energy and the oscillator strength with respect to the modulating electric field [13]. At the flat-QW condition, the highest transition energy is expected.…”
Section: Resultsmentioning
confidence: 98%
“…Upon further increase of the reverse bias voltage, the ER exhibits a change of phase between -4 and -5 V. This phase change can be understood as follows. It has been shown that for an excitonic transition from a QW, the ER signal is related to the first derivatives of the transition energy and the oscillator strength with respect to the modulating electric field [13]. At the flat-QW condition, the highest transition energy is expected.…”
Section: Resultsmentioning
confidence: 98%
“…We thus associate this electromodulation with Ge nanoislands. In order to accurately determine the transition energies, we fit the data with a first-derivative Gaussian-type function [ 8 ]. The Gaussian line-shape analysis is appropriate for the inhomogeneous broadening related to the size fluctuations in ensemble of QDs.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Such an effect is pronounced in peculiarities of the longitudinal transport 3,4 and of the magnetotransport. 5,6 Modification of the electron states and selection rules in DQW's due to tunneling has been also observed in the interband 7,8 and intersubband 9,10 optical spectra. Transition between tunnel-coupled ground states in DQW's under THz ͑far-infrared͒ radiation were analyzed.…”
Section: Introductionmentioning
confidence: 86%